1992
DOI: 10.1111/j.1547-5069.1992.tb00239.x
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Concept Analysis of Spiritual Perspective, Hope, Acceptance and Self‐transcendence

Abstract: This paper seeks to clarify four previously elusive concepts of concern to nurses: spiritual perspective, hope, acceptance and self-transcendence. Simultaneous concept analysis (SCA), a method developed by the authors, was used to generate a process model of antecedents, critical attributes and outcomes of all four concepts. This resulted in refined theoretical definitions for each concept. Interrelationships that became apparent among the concepts are discussed and implications of these interrelationships for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
146
0
4

Year Published

1994
1994
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 161 publications
(152 citation statements)
references
References 35 publications
2
146
0
4
Order By: Relevance
“…In Western middle-class societies, it is described as being action-oriented and goaldriven (Haase, Britt, Coward, & Leidy, 1992). However, in other contexts, hope may be associated with a codified set of beliefs, an outgrowth of people's personal relationships with God, connection to some higher power, trust in a responsible government, and even with superstitions (Hobfoll, BriggsPhillips, & Stines, 2003;Smith, Pargament, Brant, & Oliver, 2000).…”
Section: Instilling Hopementioning
confidence: 97%
“…In Western middle-class societies, it is described as being action-oriented and goaldriven (Haase, Britt, Coward, & Leidy, 1992). However, in other contexts, hope may be associated with a codified set of beliefs, an outgrowth of people's personal relationships with God, connection to some higher power, trust in a responsible government, and even with superstitions (Hobfoll, BriggsPhillips, & Stines, 2003;Smith, Pargament, Brant, & Oliver, 2000).…”
Section: Instilling Hopementioning
confidence: 97%
“…Meaning in life, or making sense of what is happening, is viewed as an essential component of spirituality (Carroll, 2001;Govier, 2000;Newshan, 1998), possibly even its defining characteristic (Kendrick and Robinson, 2000;Nino, 1997). Haase et al (1992) concluded that meaning in life is an outcome of spiritual perspective. Mental health patients and families have defined spiritual care as acknowledging the individual's sense of meaning and purpose (Greasly, Chiu, and Gartland, 2001).…”
Section: Research Questionmentioning
confidence: 98%
“…Haase, Britt, Coward, Leidy, and Penn (1992) identified the defining attributes of spiritual perspective as connectedness, belief, and creative energy. Hospice nurses in Carroll's study (2001) noted that spirituality was more than religious expression and included relationships with others and with God or the universe.…”
Section: Degree To Which I Feel Close To God or A Higher Powermentioning
confidence: 99%
“…47 Spirituality is considered an individual's search for meaning and purpose in life 47 based on belief in and a feeling of interconnectedness with a power greater than self. 48 Adequate dietary intake is essential for optimal health in all individuals. 15 Unfortunately, overweight is prevalent among people with MS, 49 as is malnutrition.…”
Section: Discussionmentioning
confidence: 99%